Evaluating The Antibody Titer Against Hepatitis-B In Healthcare Workers: A Cross-Sectional Study At A Tertiary Care Centre - Kumar, Deepak; Agarwal, Roshni; Rawat, Pratima; Afaq, Nashra; Srivastava, Divya (Journal of Neonatal Surgery, 2025)
INTRODUCTION: In addition to being the most contagious blood-borne virus, hepatitis B is also the only one that may be avoided with immunisation. Healthcare Workers' (HCWs') immunisation rates against Hepatitis B are extremely low in developing nations for a number of reasons. For a number of reasons, healthcare workers (HCWs) in developing countries have very low hepatitis B immunisation rates. To prevent and control the disease, healthcare workers need to be vaccinated against HBV infection. This is a high-risk disease that requires vaccination for physicians, nurses, paramedical personnel, and nursing students. AIM: To study the antibody titer against Hepatitis B in healthcare workers at a tertiary care centre. MATERIAL AND METHODS: This was a cross-sectional study carried out in the Department of Microbiology for a period of 12 months i.e., from November 2023 to November 2024. The Serum samples were collected from 72 cases and out of which 50 HCWs and their vaccination history was collected after informed consent. Those who had taken all three doses of hepatitis B were considered to be fully vaccinated those that had taken two doses as partially vaccinated. Anti HBs antibody titers were assessed by Enzyme linked immunosorbent assay method. RESULTS: Among the 50 HCWs there were 33 (66%) males and 17(47%) females recorded. It was observed that age wise distribution of Healthcare workers in which maximum number was found was in the age group of 20-30 (68%) years followed by 31-40 (26%) years of age and least in the age group of 41years of age. In the current study out of the 50 cases included, 14 (28%) were fully vaccinated that is who had completed all three doses of vaccination, 21 (42%) were partially vaccinated that who had missed their 3rd dose and 15 (30%) were unvaccinated. There was no HCW in our study who had taken only one dose of vaccination. Out of the 14 fully vaccinated HCWs, 13 (13/14) had protective anti HBs antibody titer while 1 (1/14) didn’t have protective antibody titer.. Of the 13 who had protective antibody titers, 3 (3/13) had antibody titer between 10-100 mIU/ mL and 10 (10/13) had antibody titer of more than 100 mIU/mL. Among partially vaccinated group also 4 (4/21) had protective antibody titers and all of them were between 10-100 mIU/mL. None of the unvaccinated HCWs had a protective antibody titer. CONCLUSION: The only easily measurable correlate of the vaccine induced protection is the antianti-HBs concentration serological test. Healthcare professionals, especially those who are more likely to come into contact with blood or other potentially infectious materials, require clear and well-thought-out procedures for HBV screening and vaccination.